1992
DOI: 10.1093/carcin/13.9.1643
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of repairable DNA-damage in Escherichia coli K-12 cells recovered from various organs of nitrosamine-treated mice by vitamin A, phenethylisothiocyanate, oleic acid and triolein

Abstract: The influence of various dietary constituents--phenethylisothiocyanate (PEITC), oleic acid (OA), triolein (TO), and vitamin A (ROL)--on the genotoxic activity of nitrosamines (NDMA, NDELA, NPYR) was investigated. For this purpose differential DNA repair assays with Escherichia coli K-12 strains were performed in vitro and in vivo with mice. Under in vitro conditions (liquid holding), all compounds reduced nitrosamine induced DNA-damage in the indicator bacteria in the dose range 1-10 micrograms/ml, the ranking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In previous studies, Knasmüller et al (1992;1996), using PEITC as a chemopreventive compound, observed a reduction in NDMA/NPYR-induced DNA damage in Escherichia coli K-12 and a drastic reduction of NDMAinduced micronuclei in HepG2 cells. Recently, Kassie et al (2003) showed that PEITC exerted a reduction against benzo(a)pyrene-induced DNA damage using the SCGE/HepG2 assay.…”
Section: Discussionmentioning
confidence: 92%
“…In previous studies, Knasmüller et al (1992;1996), using PEITC as a chemopreventive compound, observed a reduction in NDMA/NPYR-induced DNA damage in Escherichia coli K-12 and a drastic reduction of NDMAinduced micronuclei in HepG2 cells. Recently, Kassie et al (2003) showed that PEITC exerted a reduction against benzo(a)pyrene-induced DNA damage using the SCGE/HepG2 assay.…”
Section: Discussionmentioning
confidence: 92%
“…50 However, some studies concluded that the vegetable sprout (eg, Brussels sprout) or juice (garden and water cress) itself was protective against benzo(a)pyrene though this protection could not be attributed to the ITC content as ITCs themselves were also genotoxic at high concentrations. 52,53…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with the results of our previous studies (Arranz et al, 2006), PEITC showed stronger protective effects (67-60%, respectively) towards NPYR and NDMA-induced oxidative DNA damage than against NDBA and NPIP. Knasmüller et al (1992Knasmüller et al ( , 1996, using PEITC as a chemopreventive compound, observed a reduction in NDMA/NPYRinduced DNA damage in Escherichia coli K-12 and a drastic reduction on NDMA-induced micronuclei in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%